Efektivitas Serum Lidah Buaya (Aloe vera) terhadap Peningkatan Laju Pertumbuhan Rambut dan Sun Protection - Bella Sasmiyandri; Erwin Samsul; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Aloe vera has the potential to increase hair growth rate and sun protection so it is suitable to be formulated in serum. The purpose of this study was to produce a serum formula that meets the standards and produce a serum that has an effect in increasing hair growth rate and sun protection.This study was conducted to make aloe vera serum formula in third variation of the active substance and do a physical evaluation. Data from the physical evaluation test results and for hair growth and sun protection using analyzed statistic. The test results aloe vera serum organopetic clear white with a thick consistency and oleum rosae fragrance. Aloe vera serum have a homogenity dispersion with a viscosity of between 0.023 to 0.058 (Pa.s), the pH value between 5.7 to 6.1 and the spreadability between 6-7 cm. Aloe vera serum is stable for 3 weeks storage at room temperature. Aloe vera serum seen qualitative and quantitative has the effect of hair growth that is equivalent to the positive control (minoxidil) in the treatment for 21 days, and sun protection don’t have effect.